Cytopathology of a Rare Case of Osteosarcoma in a Murrah Buffalo (Bubalus Bubalis) - Leishangthem, Geeta D.; Jaiswal, Vikas; Gupta, Kuldip; Singh, Nittin D.; S. Randhawa, Swaran (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
Osteosarcomas are the malignant tumors of bones that may arise directly from bone or metastasis from other organs. There is involvement of various cells like osteoblast, chondroblast, fibroblast, etc. Osteosarcomas are commonly reported in dogs and cats but rarely in large animals. Benign tumors are much more common in large animals than sarcomas (Thompson and Pool, 2002). There are very few reports on osteosarcoma in cattle (Naghshineh et al., 1991; Plumlee et al., 1993; Prins et al., 2012; Micheloud et al., 2015; Santos et al., 2016). However, rarely observed in buffaloes (Silveira et al., 2010). The present communication reports a rare case of metastatic osteoblastic osteosarcoma involving the trachea of a Murrah buffalo through a cytological approach using Fine Needle Aspirates (FNA).